The Influence of Story Impressions Learning Strategy Based on Animated Videos on Students' Narrative Text Viewing and Listening Skills - Muhamad Rendi Gustiawan; Hera Wahdah Humaira (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aimed to examine the effect of an animation video–based story impressions learning strategy on students’ narrative text viewing skills in Grade VIII of SMP Negeri 15 Kota Sukabumi during the 2025/2026 academic year. The research was conducted in the even semester of the 2025/2026 academic year at SMP Negeri 15 Kota Sukabumi. The population consisted of all eighth-grade students, with a total sample of 60 students divided into an experimental group of 29 students and a control group of 31 students. This study employed a quantitative approach using a true experimental design with a post-test only control design. The research instruments included a viewing skills test, observation, and documentation. Data were analyzed using the nonparametric Mann–Whitney U test. The results indicated that students in the experimental group demonstrated better narrative text viewing skills than those in the control group. The mean score of the experimental group was higher than that of the control group. The Mann–Whitney U test showed an Asymp. Sig. (2-tailed) value of 0.000, which is lower than 0.05. Therefore, it can be concluded that the animation video–based story impressions learning strategy has a significant effect on the narrative text viewing skills of Grade VIII students at SMPN 15 Kota Sukabumi.